2017
DOI: 10.1080/02602938.2017.1356265
|View full text |Cite
|
Sign up to set email alerts
|

The role of assessment feedback in developing academic buoyancy

Abstract: The University of Gloucestershire accepts no liability for any infringement of intellectual property rights in any material deposited but will remove such material from public view pending investigation in the event of an allegation of any such infringement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Out of 39 faculty, 19 provided additional feedback, which reinforced the highest scores about the accurate feedback from the reviewers. This finding was consistent with the literature showing that individual and constructive feedback receive positive results and support future student performance (Ahmed Shafi et al, 2018;Toit, 2012).…”
Section: Measures Of a Quality Processsupporting
confidence: 92%
“…Out of 39 faculty, 19 provided additional feedback, which reinforced the highest scores about the accurate feedback from the reviewers. This finding was consistent with the literature showing that individual and constructive feedback receive positive results and support future student performance (Ahmed Shafi et al, 2018;Toit, 2012).…”
Section: Measures Of a Quality Processsupporting
confidence: 92%
“…In short, balanced critical feedback helps students to regulate their emotions. When taken together, these approaches could positively impact academic buoyancy (Shafi et al 2018), enhancing learning outcomes.…”
Section: Implications For Practicementioning
confidence: 99%
“…The inventory is designed to help students reflect on their academic buoyancy skills (e.g., planning after academic setbacks) and to assist students and teachers in developing students’ buoyancy skills over time. Other researchers have found that teachers may be able to support student buoyancy by incorporating key buoyancy elements into their everyday feedback process (ahmed Shafi et al, 2018). For example, providing clear reasoning behind the grades students received, dedicating time in class postfeedback to let students formulate an action plan based on the feedback, and helping students to manage their emotions may help students to bounce back following negative academic feedback (ahmed Shafi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have found that teachers may be able to support student buoyancy by incorporating key buoyancy elements into their everyday feedback process (ahmed Shafi et al, 2018). For example, providing clear reasoning behind the grades students received, dedicating time in class postfeedback to let students formulate an action plan based on the feedback, and helping students to manage their emotions may help students to bounce back following negative academic feedback (ahmed Shafi et al, 2018). Importantly, this feedback process is in line with other research suggesting that academic buoyancy can be supported through cognition, behavior, and emotion management systems.…”
Section: Discussionmentioning
confidence: 99%